2023
DOI: 10.3390/plants12020296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Cryptoconcatones to α-Tubulin and Related Pironetin Analogues

Abstract: Cryptoconcatones A-L represent a series of 12 dihydropyrone derivatives isolated from the evergreen tree Cryptocarya concinna Hance, which is well distributed in southeast Asia. The lead compound in the series, cryptoconcatone L, has revealed antiproliferative activity against cultured cancer cells but its mechanism of action remains unknown. Based on a structural analogy with the anticancer natural product pironetin, which is well known for binding covalently to α-tubulin and for functioning as a microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…This moiety can be found in plagiochilin Q and recently, we showed that a related series of natural products with a 5,6-dihydro-α-pyrone unit, the cryptoconcatones, can function as α-tubulin-binding agents. Notably, we identified cryptoconcatones F and L as robust α-tubulin binders capable of forming covalent protein adducts [38]. We also evidenced the cytotoxic lactone spicigerolide with a pyranone moiety as a tubulin binder.…”
Section: Discussionmentioning
confidence: 74%
“…This moiety can be found in plagiochilin Q and recently, we showed that a related series of natural products with a 5,6-dihydro-α-pyrone unit, the cryptoconcatones, can function as α-tubulin-binding agents. Notably, we identified cryptoconcatones F and L as robust α-tubulin binders capable of forming covalent protein adducts [38]. We also evidenced the cytotoxic lactone spicigerolide with a pyranone moiety as a tubulin binder.…”
Section: Discussionmentioning
confidence: 74%
“…Same models in panels (d-f) for compound (5). The modeling analysis was performed as previously described in [109,110]. The docking process has been described previously [109,110].…”
Section: Potential Molecular Targets Of Prieurianin and Analogsmentioning
confidence: 99%
“…The modeling analysis was performed as previously described in [109,110]. The docking process has been described previously [109,110]. The docking analysis was performed with Hsp47 (PDB code 3ZHA [111]), keeping the following amino acids totally flexible: Arg222, Tyr245, Asp247, Met271, His273, Leu381, Tyr383, Asp385, His386 and Arg11 (E collagen unit).…”
Section: Potential Molecular Targets Of Prieurianin and Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, one of the potential mechanisms could be a direct binding of the compound to α-tubulin, in particular to the pironetin-binding site which is known to accommodate compounds bearing a dihydro-pyrone moiety [ 65 , 66 ]. This moiety can be found in plagiochilin Q, for example, and recently, we have shown that natural products with a 5,6-dihydro-α-pyrone unit (cryptoconcatones) can function as α-tubulin-binding agents [ 67 ]. Based on these considerations, we have initiated binding studies of plagiochilins to α-tubulin and the first information obtained by molecular docking look interesting.…”
Section: Pharmacological Properties and Mechanism Of Action Of The Pl...mentioning
confidence: 99%